HPV-positive Squamous Cell Carcinoma of the Larynx, Oral Cavity, and Hypopharynx: Clinicopathologic Characterization With Recognition of a Novel Warty Variant. (May 2020) - Rooper, Lisa M.; Windon, Melina J.; Hernandez, Tahyna; Miles, Brett; Ha, Patrick K.; Ryan, William R.; Van Zante, Annemieke; Eisele, David W.; D'Souza, Gypsyamber; Fakhry, Carole; Westra, William H.
Abstract : Human papillomavirus (HPV) is a principal driver for most oropharyngeal squamous cell carcinomas (OPSCCs), where it is strongly associated with improved survival. HPV is much less frequently detected in squamous cell carcinomas arising in nonoropharyngeal sites (non-OPSCCs), and its pathogenic role and prognostic value in these tumors is unclear. We evaluated the clinicopathologic features of 52 non-OPSCCs considered HPV-positive based upon p16 immunohistochemistry and direct HPV detection using RNA in situ hybridization (ISH), DNA ISH, or real-time DNA polymerase chain reaction. The HPV-positive non-OPSCCs were from the larynx (n=27), oral cavity (n=21), and hypopharynx (n=4). While most cases (n=34, 65%) showed classic histologic features of HPV-positive OPSCC, including endophytic growth, minimal keratinization, and hyperchromatic nuclei without koilocytic changes, a subset (n=13, 25%) were characterized by exophytic growth, exuberant surface hyperkeratosis and parakeratosis, marked nuclear pleomorphism, and prominent koilocytic atypia. These antithetical features were highly reminiscent of the warty variant of HPV-positive squamous cell carcinoma described in anogenital sites. Compared with tumors without warty features, the warty tumors presented at lower stage and were not associated with lymph node metastasis, local recurrence, or distant spread (4 y disease-free survival of 100% vs. 66%, P =0.069). The presence of transcriptionally active HPV as detected by RNA ISH suggests a pathogenic role for HPV in these nonoropharyngeal sites. While most HPV-positive non-OPSCCs are morphologically similar to their tonsillar counterparts, this study highlights a previously unrecognized warty variant that may be associated with a highly favorable clinical outcome.